A reliable framework for satellite networks achieving energy requirements. (December 2021) - Geng, Sunyue; Liu, Sifeng; Fang, Zhigeng; Gao, Su
Abstract: Satellite networks with the advantage of fast transmission and global coverage are treated as significant infrastructures. They can provide a variety of services, especially those concerned real-time requirements, such as voice communication in which information is bound to be delivered within the specified time. In order to facilitate the smooth implementation of these services, operators must take actions to ensure reliable data transfer while considering on-board energy limitation. Moreover, due to the fact that data about random services is processed on satellites and transmitted over links, the uncertainty of data transfer needs to be considered. This paper presents a new framework based on queuing graphical evaluation and review technique (Q-GERT) to address these problems. Firstly, an approach is introduced to describe the transmission process under uncertainty, in order to give an accurate assessment of satellite performance. Secondly, with the help of reliability block diagram, four practical structures are designed for data transfer to guarantee satellite availability and network stability. Finally, a routing protocol considering energy requirements is proposed to enhance both global and local reliability. Case analysis demonstrates that the proposed framework compared with state-of-the-art algorithms achieves high reliability and energy efficiency. Highlights: An approach to describe the transmission process under uncertainty. Four structures for data transfer to guarantee satellite availability and network stability. A routing protocol achieving energy requirements to improve global and local reliability.